Pelletização do bagaço de cana-de-açúcar: estudo das propriedades do produto e rendimento do processo - Almeida, Leonardo Ferreira Pedroso de (2015)
Properties of pellets used as biomass fuels are essential to the performance of thermochemical processes, such as combustion, gasification and pyrolysis. These properties can affect aspects related to transportation, storage, handling, power conversion, emissions into the environment as well as variables to be controlled during the pelletizing process, directly influencing the energy consumption and production cost. This paper presents a study in a Brazilian industry of sugarcane bagasse pellets in order to determine the main properties of pellets and process variables. The objective of this work is to characterize within the pelletizing process the main physical, chemical and mechanical properties on the raw material and final product, as well as knowing the mass flows, energy consumption and cost involved in each step of the process and its variations. As the first part of the results, it was conclude that the properties of the sugarcane bagasse pellets analyzed as diameter, length, moisture, density, durability, amount of fine, calorific value, chemical elements and ash content are not full compliance with other scientific work and international marketing standards and quality pellets biomass. Secondly, one can know the rate of material consumption and production of pellets, energy consumption and costs for each step of the production process as drying, grinding and pelletizing. Finally, a mathematical function in which the power consumption and production costs grow exponentially with the variation of moisture of the raw material entry was found.